P-043 A RETROSPECTIVE OUTCOME REVIEW OF THE USE OF EGIS ACELLULAR DERMAL MATRIX DURING ABDOMINAL WALL RECONSTRUCTION. (13th October 2022) - Shaw, A; Avrova, A; Ramesh, A; Mann, T; Venkatasubramanian, A; Moinuddin, Z; Van Dellen, D
Abstract: Aim: We aimed to demonstrate the relative safety profile of an established non-crosslinked porcine acellular dermal matrix (ADM) during abdominal wall reconstruction. Material & Methods: Individual real-world safety data on specific mesh products are often lacking. With recent media scrutiny over the use of mesh, we sought to quantify outcomes and demonstrate the safety of a specific ADM (reference 1). A retrospective casenote-based outcome analysis was performed on patients who underwent mesh augmentation during abdominal wall reconstruction from two NHS institutions. Both elective and emergency patients were included from January 2018 to December 2021. Results: Fifty-five patients were included in the study across two NHS specialist hernia centres. We identified a mean wound infection rate of 14.2% (range 2–22%) with a median follow up of 9 months (range 3–18 months). Hernia recurrence rate was 10.4% (range 5–22%). We found 7 patients (12%) developed a seroma, 1 of whom required seroma aspiration. Only 4 patients (7%) had post-operative dehiscence requiring further intervention, all of whom had Ventral Hernia Working Group (VHWG) Grade 3 or 4 wounds pre-operatively. Conclusions: Our data supports the continued use of a widely available ADM for abdominal wall reconstruction in both elective and emergency cases, highlighting its positive relative safety profile.